Projected Time for the Elimination of Cervical Cancer Under Various Intervention Scenarios: Age-Period-Cohort Macrosimulation Study - Yi-Chu Chen; Yun-Yuan Chen; Shih-Yung Su; Jing-Rong Jhuang; Chun-Ju Chiang; Ya-Wen Yang; Li-Ju Lin; Chao-Chun Wu; Wen-Chung Lee (JMIR Publications, 2024)
BackgroundThe World Health Organization aims for the global elimination of cervical cancer, necessitating modeling studies to forecast long-term outcomes. ObjectiveThis paper introduces a macrosimulation framework using age-period-cohort modeling and population attributable fractions to predict the timeline for eliminating cervical cancer in Taiwan. MethodsData for cervical cancer cases from 1997 to 2016 were obtained from the Taiwan Cancer Registry. Future incidence rates under the current approach and various intervention strategies, such as scaled-up screening (cytology based or human papillomavirus [HPV] based) and HPV vaccination, were projected. ResultsOur projections indicate that Taiwan could eliminate cervical cancer by 2050 with either 70% compliance in cytology-based or HPV-based screening or 90% HPV vaccination coverage. The years projected for elimination are 2047 and 2035 for cytology-based and HPV-based screening, respectively; 2050 for vaccination alone; and 2038 and 2033 for combined screening and vaccination approaches. ConclusionsThe age-period-cohort macrosimulation framework offers a valuable policy analysis tool for cervical cancer control. Our findings can inform strategies in other high-incidence countries, serving as a benchmark for global efforts to eliminate the disease.